MODULATORY EFFECTS OF CURCUMIN ON ANTIOXIDATIVE ENZYMES IN SUBMANDIBULAR GLAND OF MALE MICE DURING AGING. - WALVEKAR M .V.; SARVALKAR P.P.; POL S.B. (International Journal of Pharma and Bio Sciences, 2013)
Antioxidative effect of curcumin was examined to determine its therapeutic role in mice experimentally exposed to D-galactose induced oxidative stress. Curcumin treatment (30mg/kg body weight daily for 30 days, orally) along with and also after treatment of 5% D-galactose [0.5ml (sc)] was found to have a protective effect on D-galactose induced oxidative stress parameters namely Superoxide dismutase(SOD), Catalase (CAT), Glutathione peroxidase (GPx) activities in the submandibular salivary glands. Post treatment with curcumin in curative group I increased the level of all the three antioxidative enzymes in submandibular glands (SMG), while in curative (45 Days) group II the levels declined. Study indicates that curcumin treatment has a protective effect therefore can be used as therapeutic agent. Our study indicates that curcumin besides being an effective antioxidant may exert its protective effect through its routine dietary intake against oxidative stress. However, prolonged administration may cause damage due to its accumulation in cells.